Measurement of the Bs0 lifetime in the exclusive decay channel Bs0 → J/ψφ - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, D. L.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahmed, S. N.; Ahn, S. H.; Alexeev, G. D.; et al. (American Physical Society (APS), 2005)
Using the exclusive decay Bs0 → J/ψ (μ+μ-)φ (K+K-), we report the most precise single measurement of the Bs0 lifetime. The data sample corresponds to an integrated luminosity of approximately 220 pb-1 collected with the DO detector at the Fermilab Tevatron Collider in 2002-2004. We reconstruct 337 signal candidates, from which we extract the Bs0 lifetime, τ(Bs0) = 1.444-0.090+0.098(stat) ± 0.020(sys) ps. We also report a measurement for the lifetime of the B0 meson using the exclusive decay B0 → J/ψ(μ+μ-) K*0(&92)(K+π-). We reconstruct 1370 signal candidates, obtaining τ(B0) = 1.473 -0.050+0.052(stat)±0.023(sys) ps, and the ratio of lifetimes, τ(Bs0)/τ(B0) = 0.980 -0.0.710.076(stat) ± 0.003(sys). © 2005 The American Physical Society.